2019
DOI: 10.1158/2159-8290.cd-18-1398
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Neurobiology and the War of Nerves in Cancer

Abstract: Nerves are emerging regulators of cancer progression. Cancer cells induce the outgrowth of nerves in the tumor microenvironment through the release of neurotrophic factors, and in return nerves liberate neurotransmitters that activate cancer growth and dissemination. Although sympathetic nerves drive tumor angiogenesis via the liberation of noradrenaline, sensory and parasympathetic nerves stimulate cancer stem cells. Interestingly, recent evidence indicates that parasympathetic nerves can eventually inhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(163 citation statements)
references
References 81 publications
2
161
0
Order By: Relevance
“…In a seminal study, autonomic nerves were shown to have a critical role in the development and spread of prostate cancer and since this study, innervation has been shown to be an important component of the development of gastric, pancreatic and other cancers (Faulkner, Jobling, March, Jiang, & Hondermarck, 2019;Magnon et al, 2013). How tumors become innervated is unknown with most research focusing on the attraction of neurons and their potential regulation of the tumor microenvironment (Faulkner et al, 2019).…”
Section: Scs As Promoters Of Tissue Regenerationmentioning
confidence: 99%
“…In a seminal study, autonomic nerves were shown to have a critical role in the development and spread of prostate cancer and since this study, innervation has been shown to be an important component of the development of gastric, pancreatic and other cancers (Faulkner, Jobling, March, Jiang, & Hondermarck, 2019;Magnon et al, 2013). How tumors become innervated is unknown with most research focusing on the attraction of neurons and their potential regulation of the tumor microenvironment (Faulkner et al, 2019).…”
Section: Scs As Promoters Of Tissue Regenerationmentioning
confidence: 99%
“…Perineural niche forms a specific background for cancer cells providing a favorable microenvironment for their survival and development. Cancer cells in perineural space are metabolically active with a higher proliferation ability and reduced apoptosis [18,73].…”
Section: Pni In Pcmentioning
confidence: 99%
“…The analysis performed on mice xenografts injected with PC-3 human PC cell line revealed that both tumor-infiltrating sympathetic fibers and intratumoral parasympathetic fibers arise from normal prostate tissue [30]. Moreover, sympathetic stimulation via β2adrenergic receptors seems to have a great impact on an-Pathobiology 2020;87:87-99 DOI: 10.1159/000505437 giogenesis, which in part explains anticancer activity of beta-blockers [18].…”
Section: Axonal Network In Tme and Nerve Fiber Density In Pcmentioning
confidence: 99%
See 2 more Smart Citations